2010
DOI: 10.4028/www.scientific.net/amr.92.271
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Nanocrystalline Ag-Cu Supersaturated Solid Solution by Mechanical Alloying

Abstract: Nanocrystalline Ag-28Cu supersaturated solid solution is prepared by mechanical alloying (MA) using a planetary ball mill. The mechanical alloyed powders are characterized by x-ray diffraction (XRD), scanning electron microscopy (SEM), high resolution transmission electron microscopy (HRTEM) and differential scanning calorimeter (DSC). XRD patterns show that the main peak of Ag-28Cu supersaturated solid solution exists at about 2θ=39° when the milling time is 30h. HRTEM images show that the grain sizes of as-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…The peak positions of Cu and Ag do not differ significantly with each other, however, the shifting of the peaks is noticed. This observation indicates the formation of the Ag(Cu) solid solution [13]. The solid solution appeared after 40 h of milling at 2θ = 39.2 o .…”
Section: Resultsmentioning
confidence: 74%
“…The peak positions of Cu and Ag do not differ significantly with each other, however, the shifting of the peaks is noticed. This observation indicates the formation of the Ag(Cu) solid solution [13]. The solid solution appeared after 40 h of milling at 2θ = 39.2 o .…”
Section: Resultsmentioning
confidence: 74%
“…The eutectic Ag-28 Cu alloys present high scientific interest, as recent research proved [15,16]. As L. Li et al report in their research [15], the melting point of the eutectic alloy is 783,8 0 C and the Ag-rich and Cu-rich phases of the eutectic are metastable after aging treatment; after the annealing treatment at (215...415) 0 C the eutectic becomes stable which is stated by the same researchers. Because of the high ductility of Ag-Cu system, a process control agent (PCA) is requested during the MA.…”
Section: Introductionmentioning
confidence: 78%
“…Because of the high ductility of Ag-Cu system, a process control agent (PCA) is requested during the MA. But, along Li's research, he points out the inconvenient represented by the low efficiency of the stearic acid used as PCA regarding the powder mixture (Ag + Cu) refinement [16].…”
Section: Introductionmentioning
confidence: 99%
“…Previous works have shown that annealing treatment of powders after milling or high temperatures during milling inhibit the formation of SSS as it produces the precipitation of second more stable phases (Schwarz, 1995). Other studies indicate that varying other milling parameters such as the use of Process Control Agents (PCA) and controlled atmospheres impact greatly the synthesis of SSS (Li et al, 2010). There is also contradicting evidence concerning the use of Hume-Rothery rules to predict the formation of SSS for the MA process (Moumeni et al, 2006;Bansal et al, 1994).…”
Section: Introductionmentioning
confidence: 99%